Improving Students’ Religious Character in Geography Learning by Using Problem Based Learning Model on Natural Disaster Adaptation and Mitigation in State Senior High Schools in Mandau District - Andriani, Yeni (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Abstract This research was aimed to describe the development os students’ religious character in Geography Learning Pby using Problem Based learnig model on the materials of natural disaster adaptation and mitigation in State senior high schools (SMAN) in Mandau District. The data showed students’ low religious character in Geography learning. One of the causes is inappropriate learning model implemented by the teacher. in Geography laerning, a teacher should be able to develop students’ religious character in the learning process so that the purpose of character based education can be achieved. To solve this problem, the teacher implemented problem based learning model because this model was able to improve students’ religious character in Geography learning. This research employed mixed method research (Sugiyono, 2012). the participants of this research were Geography teachers, students, Education Office and Principlas. techniques of data collection were observation and interview. The data was then analyzed by calculating its percentage, scoring and followd by data reduction, data interpretation, data presentation and conclusion. All of the process was conducted to obtaine informations related to Problem Based learning model implementation on Geography subject in SMAN of mandau Distrisct. The result of the research concluded that students’ religious character could be improved through the implementation of Problem Based Learning model in Geography classroom in SMAN of Mandau District.